Open thoracotomy for pneumothorax - Lazopoulos, Achilleas; Barbetakis, Nikolaos; Lazaridis, George; Baka, Sofia; Mpoukovinas, Ioannis; Karavasilis, Vasilis; Kioumis, Ioannis; Pitsiou, Georgia; Papaiwannou, Antonis; Katsikogiannis, Nikolaos; Mpakas, Andreas; Tsakiridis, Kosmas; et al. (Journal of Thoracic Disease; Vol 7, Supplement 1 (February 05, 2015): Journal of Thoracic Disease [(dedicated to) 2014 Pan Hellenic Congress on Respiratory and Occupational Chest Diseases], 2015)
A thoracotomy is an incision into the pleural space of the chest. It is performed by surgeons (or emergency physicians under certain circumstances) to gain access to the thoracic organs, most commonly the heart, the lungs, or the esophagus, or for access to the thoracic aorta or the anterior spine. This surgical procedure is a major surgical maneuver it is the first step in many thoracic surgeries including lobectomy or pneumonectomy for lung cancer and as such requires general anesthesia with endotracheal tube insertion and mechanical ventilation, rigid bronchoscope can be also used if necessary. Thoracotomies are thought to be one of the most difficult surgical incisions to deal with post-operatively, because they are extremely painful and the pain can prevent the patient from breathing effectively, leading to atelectasis or pneumonia. In the current review we will present the steps of this procedure.